Analisis Distribusi Pendapatan Dan Tingkat Kemiskinan Nelayan Di Kecamatan Sibolga Selatan Kota Sibolga Sumatera Utara - Nurhidayah, Khairunnisa; Adul Rauf; Salmiah (JURNAL AGRICA, 2024)
Fishermen are a group of people whose lives depend directly on sea products. Most of them are dominated by the profession of fishermen and are still in poverty. The poverty of fishermen as measured by the lack of wages income for the distribution of clothing, food and boards in the family's responsibility. This study aims to analyze the income distribution of fishermen, the poverty level of fishermen and analyze the factors that influence fishermen's expenditure in Sibolga Selatan District. The research method uses an analysis of the inequality indicator Gini coefficient (Gini Ratio) adjusted to the Lorenz Curve and World Bank criteria, BPS poverty line criteria (2020), Multiple Linear Regression Analysis. The results of the research show that the level of inequality in the distribution of fishermen's income according to the Gini coefficient value indicator is in the low category, while according to World Bank indicators it is in the low inequality category, namely 69 fishermen in the lower middle category and 5 fishermen in the low income category. Apart from that, according to the BPS poverty line criteria (2020), the proportion of poor fishermen is 3 fishermen. The results of this research also show that fishermen's expenses are influenced by the income and number of fishermen's dependents.